Strategies for selecting perforator vessels for transverse and oblique DIEP flap in male pediatric patients: Anatomical study and clinical applications - He, Jiqiang; Cui, Huairui; Qing, Liming; Wu, Panfeng; Guliyeva, Gunel; Yu, Fang; Tang, Maolin; Tang, Juyu (Frontiers in Pediatrics, 2022)
Background: Transverse and oblique deep inferior epigastric artery perforator (DIEP) flaps are widely used in breast, lower extremity, urogenital, head and neck reconstruction. In this report, we present our experience with selecting perforator vessels for transverse and oblique DIEP flaps based on an anatomical study and clinical cases. Materials and methods: A detailed anatomical study of the DIEP flap was carried out using a standardized injection of lead oxide in 10 fresh cadavers. Additionally, thirty-five male pediatric patients (age 5–12 years) underwent lower extremity reconstruction with a DIEP flap. A transverse DIEP flap was used when the defect template did not exceed zone IV, while an oblique DIEP flap was used when the defect template exceeded zone IV. Results: Perforators located below the umbilicus in zones I and II were rich in transverse anastomoses across the midline of the abdominal wall, which is the basis for the transverse DIEP flap. Perforators lateral to the umbilicus in the zone I had true anastomoses with the musculophrenic artery, the morphological basis for the oblique DIEP flap. The DIEP flap design was transverse in 20 patients and oblique in 15. Flap sizes ranged from 8 × 4.5 cm2 to 24 × 9 cm2. One oblique DIEP flap was necrosed totally, and it was repaired by a latissimus dorsi musculocutaneous flap. Conclusion: The transverse DIEP flap design based on the perforator located below the umbilicus in the zone I is recommended for small skin and soft tissue defects. We recommend the use of the oblique DIEP flap design based on the perforator lateral to the umbilicus in the zone I as an extended flap to reconstruct large tissue defects.